ANALYSIS OF BOD LEVELS IN LABORATORY WASTE USING THE PHYTOREMEDIATION METHOD OF WATER HYACINTH (Eichornia Crassipes) - Malina, Lina; Rasyidah, Rasyidah; Ramadhani, Ahmad Akbar (Universitas Lambung Mangkurat, 2024)
Laboratory wastewater is characterized by significant pollutants, including surfactants, phosphates, organic compounds, and inorganic compounds, leading to elevated BOD levels. BOD (Biological Oxygen Demand) serves as a key parameter for assessing the likelihood of pollution in waste materials. The higher the BOD level, the greater the potential for pollution. The utilization of phytoremediation technology with water hyacinth plants presents a promising alternative for the removal of waste pollutants, harnessing natural resources that are frequently regarded as weeds. This study thus seeks to examine BOD levels, the impact of water hyacinth quantity and waste exposure duration, and the effectiveness of the water hyacinth phytoremediation technique in lowering BOD levels in laboratory waste. This study’s benefits are to provide information on BOD level analysis, examine the impact of water hyacinth quantity and the duration of waste exposure, and assess the effectiveness of the water hyacinth phytoremediation method on BOD levels in laboratory waste. The employed research method is experimental, utilizing phytoremediation with water hyacinth plants, structured as a Factorial Randomized Block Design (RAK) with two factors and three replications. The variations consisted of 5, 10, and 15 plant clumps, with exposure durations of 3, 6, and 9 days. BOD levels were determined using the SNI 6989.72: 2009 method for the Biochemical Oxygen Demand/BOD test. The study results demonstrated an efficiency in reducing BOD levels ranging from 83.60% to 96.33%. The number of water hyacinth clumps and the duration of waste exposure had a substantial impact on the reduction of BOD and COD, with a significance level of less than 0.01. The effectiveness of the water hyacinth phytoremediation method in reducing BOD levels in laboratory waste achieved a notable N gain score of 93.27%. In conclusion, the efficiency of BOD reduction attained 96.33%. Furthermore, an increased quantity of water hyacinth plants and prolonged exposure to waste would further diminish BOD levels, indicating that the water hyacinth phytoremediation technique is effective in lowering BOD levels in laboratory waste.